KNOWING ABOUT HUMAN AND COMPUTER INTERACTION - Dewi Agushinta Rahayu; Dyah Pratiwi (Jurnal Psikologi, 2008)
Human computer interaction is a study learning about human computer interaction and its task. Its principle is how about human and computer interactively done the task effectively. HCI is a mix study form technique and art and its involving principles, clues and methods for making evaluation from interactive system. Key words: psychology, computer science, HCI, interface